Dedifferentiated chondrosarcoma with telangiectatic osteosarcoma-like features. Issue 11 (27th October 2006) - Okada, K; Hasegawa, T; Tateishi, U; Endo, M; Itoi, E
Abstract : A 35-year-old Japanese man was admitted to the National Cancer Center, Tokyo, Japan, in December 2000, with a 2-month history of pain around the left thigh. Radiographs showed a poorly demarcated osteolytic lesion with focal mineralisation and endosteal scalloping in the left proximal femur. Biopsy showed a proliferation of highly anaplastic cells without any cartilaginous component. A wide excision of the left proximal femur with a replacement by endoprosthesis was carried out in February 2001 after treatment with methotrexate and 20 Gy radiation therapy. Pathological examination of the surgical specimen showed a focus of low-grade chondrosarcoma and the coexistence of telangiectatic osteosarcoma-like features. The patient was diagnosed with dedifferentiated chondrosarcoma with telangiectatic osteosarcoma-like features. Lung metastasis appeared in July 2001 despite an adjuvant chemotherapy including methotrexate, cis -platinum and doxorubicin. The latest follow-up study in June 2004 showed multiple lung metastases. Establishing a definitive diagnosis of dedifferentiated chondrosarcoma may be difficult with limited small biopsy specimens. Dedifferentiated chondrosarcoma should be included in the differential diagnosis of osteolytic tumours with focal calcification and endosteal scalloping even if an extraosseous tumour component is not identified.